Assessment of fetomaternal outcome following common induction methods (Foley’s catheter, dinoprostone and misoprostol) for induction of labor in low risk women with term pregnancy - M. R., Manasa; Kumar G., Sampath; Nair, Aparna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Various mechanical and pharmacological approaches available for induction of labor (IOL), have varying effectiveness. This study compared the efficacy of three common IOL methods: intracervical Foley catheter, dinoprostone, and misoprostol, in achieving timely and safe vaginal deliveries. Methods: A 12 month (March 2022 to March 2023) prospective observational study at Vydehi Institute of Medical Science and Research Centre on 60 term pregnant women undergoing IOL compared induction-to-delivery interval, post-induction Bishop scores, mode of delivery, oxytocin requirements, maternal and fetal morbidities with Foley catheter, dinoprostone gel and misoprostol induction to determine the efficacy and safety of each method. Results: The study revealed notable differences in the effectiveness of the induction methods. Dinoprostone demonstrated the shortest induction-to-delivery interval (8.13 hours) and the highest rate of vaginal deliveries (90%). Misoprostol, while slightly slower with a 12.35-hour interval, achieved 85% vaginal deliveries. While, Foley catheter group had the longest induction-to-delivery time (18.12 hours) and a lower rate of vaginal deliveries (70%). Additionally, oxytocin augmentation was required more in the Foley catheter group. Maternal and fetal complications were significantly lower in the dinoprostone and misoprostol groups, focussing their superior safety profiles. Conclusions: Pharmacological methods proved more efficient than Foley catheter in reducing induction time, improving cervical ripening, and increasing the likelihood of successful vaginal deliveries. Dinoprostone, in particular, emerged as the most efficient method with the fewest complications. However, careful monitoring is necessary to mitigate potential risks like uterine hyperstimulation, especially with misoprostol.